2019
DOI: 10.1007/s12298-019-00675-3
|View full text |Cite
|
Sign up to set email alerts
|

Ipomoea batatas: papain propeptide inhibits cysteine protease in main plant parasites and enhances resistance of transgenic tomato to parasites

Abstract: Different parasites cause severe lose in quantity and quality of crops. Many parasites develop haustorial cells and stylets that penetrate the host using secreted enzymes and mechanical pressure. Cysteine proteases are pre-pro-enzyme produced by parasites that are essential for normal parasitism. Papain is also a kind of cysteine proteases such that its propeptide segment has inhibitory properties and limits the protease activity of papain. To investigate the inhibitory effects of papain propeptide on some par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similarly, Korde et al [ 41 ] found that a synthetic 15-mer residue peptide based on the propeptide sequence of falcipain-2, a Plasmodium falciparum cathepsin L, inhibited its cognate enzyme with 10,000 times less potency than the propeptide of falcipain-2 itself [ 41 , 42 ]. Therefore, despite the enthusiasm for exploiting the C-terminal portion of propeptides for small drug design against cathepsin-like peptidases, creating the 3-D configuration that binds the substrate cleft with high affinity will be challenging [ 13 , 18 , 22 ]. More creative design methods such a cyclisation of peptides to improve their conformation, stability and activity compared to linear peptides [ 43 , 44 ] may be a future option to develop specific propeptide-based inhibitors against the cathepsin peptidases of F. hepatica that could have applications as anti-parasitic reagents against this other medically-important parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Korde et al [ 41 ] found that a synthetic 15-mer residue peptide based on the propeptide sequence of falcipain-2, a Plasmodium falciparum cathepsin L, inhibited its cognate enzyme with 10,000 times less potency than the propeptide of falcipain-2 itself [ 41 , 42 ]. Therefore, despite the enthusiasm for exploiting the C-terminal portion of propeptides for small drug design against cathepsin-like peptidases, creating the 3-D configuration that binds the substrate cleft with high affinity will be challenging [ 13 , 18 , 22 ]. More creative design methods such a cyclisation of peptides to improve their conformation, stability and activity compared to linear peptides [ 43 , 44 ] may be a future option to develop specific propeptide-based inhibitors against the cathepsin peptidases of F. hepatica that could have applications as anti-parasitic reagents against this other medically-important parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Since the N-terminal cathepsin propeptide of cysteine peptidases are highly specific and potent regulators of their cognate enzyme [13,18], they can act as useful structural templates to design active-site directed, selective, and efficient inhibitors of cathepsin peptidases [19][20][21][22]. Uncovering how propeptides bind to their cognate mature domain is, therefore, not only fundamental to understanding parasite virulence and infection, but also important in gaining information that could be exploited for anti-parasite drug design.…”
Section: Introductionmentioning
confidence: 99%